The Effectiveness Of Sharia Fintech Securities Crowdfunding (Scf Syariah) For Business Capital For Santripreneurs In Indonesia - Alfi, Rian (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2026)
This study analyses the effectiveness of Sharia Securities Crowdfunding (SCF Syariah) as an innovative solution to the capital constraints faced by santripreneurs in Indonesia. Using a Systematic Literature Review (SLR) covering the period 2020–2025, this study evaluates strategic opportunities and fundamental barriers within the pesantren ecosystem. The findings indicate that Sharia SCF possesses a competitive advantage due to its alignment with the principle of ta’awun and the implementation of profit-sharing contracts such as Mudharabah and Musyarakah, which are free from riba. However, its growth is hindered by low digital financial literacy among santri in developing business projections, regulatory gaps regarding information disclosure standards, and limited technological infrastructure in remote areas. This study concludes that Sharia SCF, through Mudharabah and Musyarakah contracts, is an innovative instrument aligned with the principle of ta’awun within the pesantren ecosystem. Although santripreneurs hold a strategic position in producing global commodities, the effectiveness of this financing remains hindered by low digital financial literacy and regulatory limitations regarding human resource standardisation and investor protection. Therefore, the success of Sharia SCF requires systemic readiness and stakeholder synergy to mitigate the risks of information asymmetry and strengthen the business accountability of Islamic boarding schools.